GOOD TEACHING PRACTICES FOR THE EDUCATIONAL INCLUSION OF EARLY CHILDHOOD IN THE SOCIAL MANAGEMENT SCHOOL, CALLED SEGUNDO DAVID PERALTA, KNOWN TOO AS "MATE COSIDO", IN RESISTENCIA, CHACO PROVINCE, ARGENTINA - Norma Elena Bregagnolo; Zulema del Carmen Nussbaum; Marina Stein (Universidad Nacional del Nordeste, 2018)
This communication is made in the framework of the research "Good Practices in Childhood Education. A case study in the Greater Resistencia-Chaco Metropolitan Area "- (UNNE), PI H007 -, by Resolution No. 984/14 - C.S. UNNE, gramed in the International Project "Curricular Design and Good Practices in Early Childhood Education: an international, multicultural and interdisciplinary vision" directed by Dr. Zabalza. It is an exploratory study, approaches pedagogical practices carried out in the Maternal and Infants Garden of the Public School of Social Management No. 1 "Latin American Heroes", whose creation was promoted by the Political - Social Movement called Territorial Movement of Liberation - MTL - . Among its aims, it is proposed to describe the teaching conceptions around the "Good Practices" in Childhood Education and to identify, analyze and make visible "Good Practices" in particular contexts. In the course of this work, it is visualized as from the different actors of this institution how they generate dynamics of participation and collaborative work with families permanently, and at the same time proposals for integration to the whole institution.